Essentials of marketing - Lamb, Charles W.; Hair, Joseph F.; McDaniel, Carl D. (Australia ; United States : South-Western College, 2001)
This book is about: The world of marketing; Analyzing marketing opportunities; Product and distribution decisions; ...
Keywords: Marketing; Management; Marketing; Marketing -- Australia -- Management